ARTIFICIAL INTELLIGENCE AND ITS ROLE IN EDUCATION (DIGITAL TRANSFORMATION AND ARTIFICIAL INTELLIGENCE, 2025)
The purpose of this study is to study the role of artificial intelligence (AI) applications in education. Applications AI in many ways solve the problem of exponential growth of modern problems that create difficulties in accessing education and training. They play an essential role in the creation of social robots (SR), smart learning (SL) and intelligent learning systems (ITS). The review shows that the education sector should also use modern teaching methods. Looking into the flow, education sector organizations need to embrace AI technology as a necessity of the day and education.
Keywords: artificial intelligence; social robots; intelligent learning; intelligent learning system; education